Miss Wading Pool Contest Thank You Letter - Ada Hibbard:::::: (1973)
A thank you letter from the Oxnard Parks and Recreation Department to Jane Tolmach thanking her for her participation in the judging of the 1973 Miss Wading Pool Contest.